2014
DOI: 10.1007/s11103-014-0190-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive regulation of rice RING E3 ligase OsHIR1 in arsenic and cadmium uptakes

Abstract: The metalloid arsenic (As) and the heavy metal cadmium (Cd) are ubiquitously found at low concentrations in the earth. High concentrations of these elements in the soil and crops are severely dangerous to human health. We attempted to retrieve the RING E3 ubiquitin ligase gene for regulating As and Cd uptakes via the ubiquitin 26S proteasome system. Semi-quantitative reverse transcription polymerase chain reaction was conducted for a total of 47 Oryza sativa RING finger protein (OsRFP) genes to assess their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Previously, we reported positive regulation of As and cadmium uptake in rice by RING E3 ligase (Lim et al ). Furthermore, it has been reported that heterologous overexpression of OsAIR1 positively regulates post germination plant growth under As(V) stress (Hwang et al ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previously, we reported positive regulation of As and cadmium uptake in rice by RING E3 ligase (Lim et al ). Furthermore, it has been reported that heterologous overexpression of OsAIR1 positively regulates post germination plant growth under As(V) stress (Hwang et al ).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, our results may provide important clues to the mechanisms of posttranslational modifications in plants that have adapted to As exposure. Previously, we reported positive regulation of As and cadmium uptake in rice by RING E3 ligase (Lim et al 2014). Furthermore, it has been reported that heterologous overexpression of OsAIR1 positively regulates post germination plant growth under As(V) stress (Hwang et al 2016).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The OsHIR1 protein interacts with the OsTIP4;1 aquaporin, mediating its proteolysis through the ubiquitin/proteasome 26S degradation pathway. 31 Therefore, according to the authors, the OsHIR1 E3 ligase protein is able to control the absorption of these metals in the plant, probably through the OsTIP4;1 protein regulation via ubiquitination. Even though aquaporin proteins have not been described as As-transporter in plants until now, Zhao et al 32 stated that some TIP channels might be permeable to As transport into the vacuoles, due to its pore structure.…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Moreover, OsHIR1 overexpression in Arabidopsis also increased the tolerance to As and Cd, when compared to wild-type plants. 31 It is important to highlight that definitive proof of involvement of OsTIP4;1 in As and Cd efflux transport to the vacuole would require the demonstration of its biochemical activity in vitro. Anyway, this was the first study to present an E3 ligase with RING domain conferring tolerance to metals in plants.…”
Section: Heavy Metal Stressmentioning
confidence: 99%